2018
DOI: 10.1111/dgd.12585
|View full text |Cite
|
Sign up to set email alerts
|

Lateral neural borders as precursors of peripheral nervous systems: A comparative view across bilaterians

Abstract: The nervous systems in most bilaterians are centralized, composed of central nervous systems (CNS) and peripheral nervous systems (PNS). Common molecular and cellular patterns of medial nerve cords have been observed in various distantly related bilaterians, suggesting deep homology of CNS. The development patterns of PNS, however, are more diverse than CNS across different phylogenetic lineages and the evolution of PNS so far has been thought to be polygenic. The molecular and cellular programs during the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 154 publications
(364 reference statements)
2
17
0
Order By: Relevance
“…Our results align with multiple lines of evidence across Bilateria showing that the function of BMP signaling in neural induction is not conserved across Bilateria (Martín-Durán et al, 2018; Zhao et al, 2019). For example, in vertebrates, formation of the dorsal neural tube relies in part on inhibition of BMP signaling by graded antagonists secreted from the organizer (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…Our results align with multiple lines of evidence across Bilateria showing that the function of BMP signaling in neural induction is not conserved across Bilateria (Martín-Durán et al, 2018; Zhao et al, 2019). For example, in vertebrates, formation of the dorsal neural tube relies in part on inhibition of BMP signaling by graded antagonists secreted from the organizer (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…Take, for example, the neural plate border in vertebrates, the embryonic domain that produces neural crest progenitors. Studies of invertebrates on both the protostome and deuterostome sides of the bilaterian tree have revealed the presence of so-called lateral neural borders that are similar to the neural plate border [120] (figure 3a). These lateral neural borders develop as part of a broad embryonic domain that instructs medial-lateral patterning of the neuroectoderm into the CNS and PNS [120].…”
Section: Ancient Origins Of Neural Crest Regulatory Mechanismsmentioning
confidence: 99%
“…Studies of invertebrates on both the protostome and deuterostome sides of the bilaterian tree have revealed the presence of so-called lateral neural borders that are similar to the neural plate border [120] (figure 3a). These lateral neural borders develop as part of a broad embryonic domain that instructs medial-lateral patterning of the neuroectoderm into the CNS and PNS [120]. Cells derived from lateral neural borders express homologues of Pax, Zic, Msx and Nkx transcription factors and give rise to migratory and non-migratory sensory neurons of the embryonic PNS, just as neural crest cells do in vertebrates [120,121].…”
Section: Ancient Origins Of Neural Crest Regulatory Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vertebrate Msx/vab-15-specified domain represents the merged expression patterns of Msx1, Msx2, and Msx3 in mouse (Duval et al, 2014;Wang, Chen, Xu, & Lufkin, 1996). BTN, bipolar tail neuron; CNS, central nervous system; DRGN, dorsal root ganglion neurons [Color figure can be viewed at wileyonlinelibrary.com] related bilaterians have revealed that they are similar in overall spatial arrangement and molecular identity mediolaterally (Denes et al, 2007;Li et al, 2017;D. Zhao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%